Artificial intelligence in skin cancer diagnosis: a literature review - Irmadita Citrashanty; Maya Wardiana (Bali Dermatology Venereology and Aesthetic Journal, 2022)
Nowadays, artificial intelligence (AI) has been integrated into various sectors including dermatology. AI offers alternative diagnostic tools for skin cancer, especially for dermatologists who are not familiar with dermoscopy and when histopathology examinations are not available. Therefore, this paper provides a review of the role and development of AI, as well as its limitations in assisting the diagnosis of skin cancer. Artificial intelligence (AI) is a computer science aiming to produce a program mimicking human cognition to analyze complex data. AI in dermatology comes in a variety of programs, such as the integration of AI in smartphone applications. From several studies, AI helps to diagnose skin cancer as early as possible resulting in early treatment and offers a more objective examination than dermoscopy which is operator-dependent. AI helps to give dermatologists consideration to perform more invasive examinations such as biopsies as well as treatment recommendations that can be done. However, AI still can not replace the ability of doctors to integrate the patient’s medical history with findings obtained from the physical examination. This breakthrough is still at an early stage which requires the support of more research with collaboration between dermatologists and computer experts.